Pluripotent Stem Cells for Livestock Health and Production - Punetha, Meeti; Bajwa, Kamlesh K.; Dua, Seema; Bansal, Sonu; Kuotsu, Vineichuno; Parashar, Atul; Selokar, Naresh L.; Kumar, Pradeep; Yadav, P.S.; Kumar, Dharmendra (Current Stem Cell Research & Therapy, 2022)
Pluripotent stem cells (PSCs) have unlimited capacity for self-renewal and differentiation so that they can potentially produce any cell or tissue of animal’s body. The PSCs derived from livestock represents a more appropriate model than a rodent for investigating human diseases due to their higher anatomical and physiological resemblance with human. Apart from that, livestock PSCs hold immense promises for innovative therapies, transgenic animal production and their biomedical interest. The realization of the full potential of PSCs, however, depends on the elucidation of the molecular mechanisms which play a critical role in the maintenance of pluripotency and reprogramming procedure remains poorly understood in livestock which in turn impedes the generation of true PSCs and their usage for clinical research. An in-depth understanding of pluripotency is extremely essential for improving health and welfare of livestock animals. Therefore, the present review focuses on the milestone achievements of PSCs in livestock animals and their potential application in health and production of livestock.
Keywords: health